Smart condominium simulation using low code programming - Tee, Yu Xuan (2025)
This project provides a smart condominium simulation architecture with a goal to reduce the gap between user interactions, real-time sensor data, and automated functionalities within the simulated environment. This architecture focusses the accessibility and user-friendliness by using low-code programming. One of the key contributions is the development of a scalable smart condominium model. The platform's modular design allows the combining of multiple devices, sensors, and functionality, which ensuring its ability to grow and develop with the development of smart condominium technology. Additionally, the use of Scalable Vector Graphics (SVG) helps to design pleasant and flexible simulation object representations. Then, another way to point out the user-friendliness is the applying of the low-code programming platform Node-RED. With this platform, individuals with different levels of coding experience can simulate out the functions and interactions between the smart home devices. It brings the ability to instantly interact with the simulation, operate virtual equipment, establish the automation rules based on simulated sensor data, and track the effects of their actions, the platform places a high priority on an interactive user experience. In the nutshell, this project enhances the field by developing an architecture for smart home simulation that is more flexible. This platform helps to develop a more sustainable and effective smart home technologies to explore the potential of smart homes. Area of Study (Minimum 1 and Maximum 2): Modelling, Simulation Keywords (Minimum 5 and Maximum 10): Smart Condominium, Simulation, Low-Code Programming using Node-RED, Scalable Vector Graphics (SVG), Smart IoT Devices.